Discounting the distant future—Data on Australian discount rates estimated by a stochastic interest rate model - Chi Truong; Stefan Trück (Data in Brief, 2017)
Data on certainty equivalent discount factors and discount rates for stochastic interest rates in Australia are provided in this paper. The data has been used for the analysis of investments into climate adaptation projects in ׳It׳s not now or never: Implications of investment timing and risk aversion on climate adaptation to extreme events׳ (Truong and Trück, 2016) [3] and can be used for other cost-benefit analysis studies in Australia. The data is of particular interest for the discounting of projects that create monetary costs and benefits in the distant future.